Analysis of Factors Affecting Customer Loyalty of Meatball Stalls in the City of Bandung - Fitriyani Fitriyani; Aryanto Aryanto; Evan Jaelani (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to analyze the influence of product quality, price, and service on customer loyalty in meatball stalls in Bandung, Indonesia. A quantitative approach was used with a survey method involving 111 active customers. The questionnaire instrument was tested for validity and reliability before being applied in regression analysis. The results show that price and service have a positive and significant effect on customer loyalty, while product quality does not. These findings indicate that customer loyalty in this culinary is more influenced by service experience and perceived economic value than by product taste quality. The study offers strategic implications for culinary business owners to focus on improving service quality and maintaining competitive pricing to sustain customer retention.